Sosialisasi Peran Apersepsi Untuk Meningkatkan Kesiapan Belajar Anak Di Sanggar Genius Yayasan Yatim Mandiri Cabang Kediri - Karimatus Saidah; Nurita Primasatya; Bagus Amirul Mukmin; Susi Damayanti (Universitas Nusantara PGRI Kediri, 2021)
The problem parents experience today is being wise parents to introduce smartphones to children. This is what makes parents a dilemma to provide smartphone facilities to children or not. Because there are two influences that will arise when parents provide smartphone facilities to children. First, the positive effect is to support online learning activities, . The second effect is the negative effect, namely the child does not explore the physical environment, the child has difficulty interacting socially, the child gets emotional easily and the memory decline due to prolonged. In this service activity, there will be counseling to parents about how to wisely introduce smartphones to children. The target of this service is the parents of Al Amin Foundation Kindergarten Kediri and carried out on November 12, 2019. Material and assistance about wisely introducing smartphones to children can generate knowledge and insights to parents on how to wisely introduce smartphones to children. A wise way to introduce smartphones to children is to allocate time for children to play smartphones, make smartphones as learning tools containing educational applications, provide assistance to children when using smartphones, and be selective in choosing smartphones for children